Green Human Resources Management: a comparative study of Japanese multinationals - Tsibana, Camila Lie (2024)
This master thesis aims to explore the Human Resources practices towards the company’s environmental efforts in Japanese multinationals. The study involves an analysis of a sample comprising four companies of Japanese capital. The first analysis approach for this thesis is to evaluate the company’s communication and environmental efforts through its published reports, information found on its websites, and third-party sources. A second approach defines the best practices for Green Human Resources Management and assesses them based on the information disclosed by these corporations. The research provides insights into the environmental concerns of the sampled companies (Toyota Motor Corporation, Mitsubishi Corporation, Honda Corporation, and Mitsui & Co.), as well as an overview of their reporting and Green Human Resources practices. Although the Social and Governance pillars within the ESG agenda are natural concerns for the Human Resources department, this study aims to delve deeper into links with less obvious direct impacts. In other words, the environmental concerns. In addition, this study also tries to find similarities and a better understanding of the scenario through the perspective of Japanese multinationals. The findings reveal that Japanese companies show a strong commitment to addressing environmental issues. They have transparent reporting but need standardization for external reporting to other institutions such as the United Nations. When it comes to Green Human Resources practices, all of the studied companies follow best practices in Green Recruiting. Overall, while companies are dedicated to environmental initiatives, there are opportunities for further standardization and improvement in certain aspects of Green Human Resources practices.